Consequences of Teenage childbearing in Peru: is the extended-school-hour-program an effective policy instrument to prevent teenage pregnancy? - Sanchez, A; Favara, M (Young Lives, 2019)
In Peru, approximately 14 out of 100 female adolescents are mothers. Teenage childbearing is a major policy concern, as most studies point to a negative impact of early fertility on maternal outcomes and on the birth and future of the children. This paper investigates the role of extended school-day programmes, primarily seen as a means of improving academic achievement, for teenage pregnancy prevention. It first reviews the literature on policy alternatives to reduce teenage pregnancy that have been evaluated in developing countries, including extended school-day programmes. Second, it describes the phenomenon of teenage pregnancy (and early marriage and cohabitation) in Peru. Third, it evaluates the impact of the Peruvian extended school-day reform (Jornada Escolar Completa, JEC) on several risk and protective factors predicting teenage pregnancy. Our results are in line with previous assessments of similar programmes in the region. We find that, on average, being a student from a JEC school leads to an improvement in reading comprehension and maths. Our findings also suggest a possible impact of JEC on teenage pregnancy via an increase in educational aspirations and psychosocial competencies. Looking at potential heterogeneous effects by gender reveals that the programme has a larger impact on male students’ school performance. It also has an impact on female´s pride and sense of agency, which might promote safer sexual behaviour through affecting females’ perceived barriers to the use of contraceptive methods and empowering them to handle situations in which they are asked to have unprotected sex. Finally, we find that JEC improves male students’ knowledge about sexual and reproductive health. This impact might further promote more responsible behaviours and ultimately be one of the channels leading to a decrease in early fertility – together with an increase in performance, aspirations and socio-emotional competencies.